Android Used in The Learning Innovation Atwood Machines on Lagrange Mechanics Methods - Shabrina Shabrina; Warsono Warsono; Heru Kuswanto (Universitas Sebelas Maret, 2017)
Android is one of the smartphone operating system platforms that is now widely developed in learning media. Android allows the learning process to be more flexible and not oriented to be teacher center, but it allows to be student center. The Atwood machines is an experimental tool that is often used to observe mechanical laws in constantly accelerated motion which can also be described by the Lagrange mechanics methods. As an innovative and alternative learning activity, Atwood Android-based learning apps are running for two experimental variations, which are variations in load in cart and load masses that are hung. The experiment of load-carrier mass variation found that the larger load mass in the cart, the smaller the acceleration experienced by the system. Meanwhile, the experiment on the variation of the loaded mass found that the larger the loaded mass, the greater the acceleration experienced by the system.